Peak load scheduling in smart grid using cloud computing - Manoj Hans; Vivekkant Jogi (Institute of Advanced Engineering and Science, 2019)
In this paper present peak, energy management attainable is feasible by monitoring real-time readings of whole loads within the college premises victimization this schedule loads so energy saving is possible. Currently, cloud computing technology offer on-line real-time monitoring knowledge, we have a tendency to create project supported cloud computing application for energy management that is employed for monitoring real time consumption of electricity and load planning. With respect to monitoring knowledge, we have a tendency to be able to plot the load curves so it'll be useful in achieving optimum energy consumption for educational institute.